Comparative analysis of paediatric and adult surgically drained dental infections at a university teaching hospital. Issue 10 (December 2020) - Mair, M.; Mahmood, S.; Fagiry, R.; Mohamed Ahmed, M.; Rajaram, K.; Baker, A.; Avery, C.
Abstract: In the United Kingdom (UK) the estimated prevalence of dental infection involving the supporting bone is 2%, and from 2014–2015 there were 2281 admissions in England alone due to dental abscess. We undertook an analysis of 184 dental abscesses that required surgical drainage, as there is surprisingly little in the literature on the subject. This was a retrospective study of 184 consecutive patients with dental abscesses who were admitted between January 2016 and September 2019. On admission, all patients had orthopantomograms (OPG) and baseline blood tests. Surgical drainage was performed under a general or local anaesthetic and a pus swab sent for culture and sensitivity. The submandibular space was the most commonly involved site and paediatric patients most often presented with buccal space abscesses. A lower molar tooth was the cause in 132 patients. White blood cells (WBC) and C-reactive protein (CRP) were both raised in 63.6% (n = 117), but were normal in 4.9% (n = 9). The remaining patients had either raised WBC (2.7%) or CRP (28.8%). Streptococcus milleri was the most common organism isolated in 66.6% (n = 42). There was no association between CRP or WBC values and duration of hospital stay. Paediatric patients had a shorter duration of admission (1.96 days vs 2.81 days) and significantly lower CRP values (120.9 vs 45.7; p = 0.001). The submandibular space was the commonest site involved and mandibular molars the most frequent source of infection. An elevated CRP value appeared to be a more sensitive indicator of infection in this study population. Adult and paediatric patients present in a different manner.